Event-based biogeography of Eusarcus dandara sp. nov. (Opiliones: Gonyleptidae), an endemic species of the Northern Atlantic Rainforest of Brazil, and its closely related species - Saraiva, Nícolas Eugenio De Vasconcelos; Dasilva, Marcio Bernardino (Zootaxa, 2016)
Here, we describe a new species of Eusarcus and reconstruct the geographical evolution of its species group based on biogeographical event-based analysis. Eusarcus dandara sp. nov. has been recorded from Alagoas state, in northeastern Brazil, which represents an important range extension of the genus to the northern Atlantic Rainforest. We performed a cladistic morphological analysis based on new data and data from a previous systematic review of the genus to reconstruct the phylogenetic placement of the new species. This analysis resulted in six most parsimonious cladograms. We performed the biogeographical reconstruction using the Treefitter 1.3B1 algorithm for the clade of eight species that includes E. dandara sp. nov., and we tested the significance of the reconstructions. We found two alternative reconstructions depended on the differences in species relationships; both were significant (0.002 ≤ p ≤ 0.019). The phylogenetic placement of the new species is consistent with some expectations based on previous biogeographical studies of Atlantic Rainforest harvestmen. Reconstructions reveal the origin of the species group in the northeast region, in the Atlantic Rainforest plus interior and dry biomes, such as the Caatinga xeric shrubland and Cerrado savanna, with subsequent dispersal to the southeast region. Harvestmen are good models to study the historical biogeography of the Atlantic Rainforest, especially those species that are endemic, like most Eusarcus. We have demonstrated a complex history of the spatial evolution of the group and the importance of the adjacent drier biomes in the evolution of endemic organisms of the Atlantic Rainforest.